Feeding habits of the Asiatic red-bellied squirrel Callosciurus erythraeus introduced in Argentina - Zarco, Agustín (2018)
Knowledge of food habits of invasive species is necessary to predict invasion success and potential interactions in the invaded community. The Asiatic red-bellied squirrel Callosciurus erythraeus has been introduced in Asia, Europe and South America. We studied feeding habits of red-bellied squirrels in Argentina in two sites 600 km apart where wild populations have become established. We used both faecal microhistological analysis and behavioural records to describe diet composition and feeding habits. We also analysed diet selection and the potential role of the squirrels as seed disperser. Squirrels consumed items from 35 species of exotic trees and shrubs and one native tree species; fruits and seeds represented the bulk of the diet in all seasons (faeces analysis: >44%; behavioural observations: >38%). Squirrels also consumed epiphytic and climbing plants, ferns, invertebrates, fungi, lichens, mosses and bird eggs. Diet composition varied throughout the year according to food availability. We did not find evidence of endozoochoric dispersal but we observed squirrels carrying and dropping nuts and acorns during transport. The consumption of a wide range of food items and species, the ability to modify the diet according to food availability, and the capacity to hoard food indicate that feeding habits of red-bellied squirrels favour their invasive potential.